Computer programming examples for chemical engineers - Ross, George, 1929- (Computer-aided chemical engineering, 1987)
Written by a chemical engineer rather than by a computer scientist, this book fills the gap between texts which teach computer languages or programming methods and chemical engineering texts which omit details of writing programs. In order to write a computer program and get it to work, general theoretical principles are not enough; one has to actually do the job. This is done in each case by first taking the reader through a manual calculation, then presenting a computer program to perform the same task. Explanation of how the program operates is given in some detail.